(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the issues related to the creation and linguistic annotation of a corpus of Uzbek texts in the official style that emerged during the independence period. It describes linguistic annotation models that enable automatic and semi-automatic analysis of official texts based on the theory of corpus linguistics. The article presents a methodology developed on the basis of research into morphological, syntactic, and semantic annotation types, as well as statistical results obtained from the corpus.